Research trends in gambling tax dynamics: A bibliometric analysis - Khithobi, Arya Teges; Margono, Hendro; Hariani, Nurul Jamila; Soegiono, Agie Nugroho (Faculty of Social and Political Science, Universitas Airlangga, 2024)
Gambling has been around for a long time and continues to evolve as it becomes integrated with video games. In its development, gambling continues to have negative impacts both economically and socially, such as unemployment, tax losses, divorce, and suicide. However, gambling can also have a positive impact, such as an increase in government revenue if taxed appropriately. This study aims to offer a thorough analysis of many publications from the last decade and monitor the progress of scientific research on gambling taxes as found in the Scopus database, utilizing VOSviewer and WordStat. In this study, the method used was bibliometric analysis. Between 2014 and 2023, a total of 132 scientific articles were dedicated to studying gambling taxes. There are a total of seven groups consisting of 111 keywords that are directly connected to gambling taxes. There are three groups of eight authors who are collaborating on a research project about gambling taxes. The study found that the University of Macau has affiliations with the majority of publications that impose gambling taxes. The United States has the biggest number of publications on the topic of gambling taxes. Studies on gambling taxes frequently confront issues of tax evasion and focus on a significant topic, namely the impact on public health and individuals. The study concluded that publications related to gambling taxes are dominated by articles from various multidisciplinary fields. This study recommends a wider range of publications and research from a more varied range of time and sources.